Environmental effects of sewage oceanic disposal by submarine outfalls: a review - Moledo de Souza Abessa, Denis; Rodarte de Figueredo Rachid, Bauer; de Oliveira Moser, Gleyci Aparecida; Fernandes Cardoso de Oliveira, Ana Júlia (O Mundo da Saúde, 2012)
Oceanic disposal systems of domestic sewage, or submarine sewage outfalls, have been historically used around the world as a solution for urban effluents, in special due to economic aspects. However, release into the ocean, in shallow or deep waters, may induce a set of negative environmental impacts, as eutrophication, toxic algal blooms, pathogenic microorganisms introduction and contamination by chemical substances which are capable of causing toxic effects to the biota and bioaccumulation. Thus, the release of untreated sewage into the sea does not constitute an adequate environmental practice; then, urban effluents should be treated in order to remove nutrients, contaminants and pathogenic organisms and avoid environmental degradation